Analysis of the History of the Islamization of Java - Irfan Julianto; Anggun khoerun Nisa; Sinta Farikhah Febriyanti; Zecky Ridwan (HISTORICAL: Journal of History and Social Sciences, 2022)
The Javanese people or more precisely the Javanese people, in cultural anthropology, are people who in their simple lives use the Javanese language with various dialects for generations. The Javanese people are those who live in the areas of Central Java and East Java, and they come from both regions. This dynamism is the belief that what they have built is the result of adaptation to struggle with nature. This Javanese culture is continuously maintained by the nobility and the nobility or Javanese intellectuals. The two cultures have their own characteristics. The peasant culture living in the countryside is a small tradition that is still dominated by the oral tradition, while the aristocratic culture has developed a tradition of writing by utilizing Hindu Buddhist religious literature. Java is Sufi Islam, namely Islam which is easily accepted and absorbed into Javanese syncreticism. And of course To me, the Sufi Islam that Peacpck meant was none other than Islam spread by walisogo figures. Islam is the source and values ​​of shari'a law. Prior to Hinduism and Buddhism, prehistoric Javanese society had embraced beliefs that matched animism and dynamism. People's view of life is directed towards the formation of a numinous unity between the real world, society and the supernatural realm which is considered sacred. Hindu-Buddhist influences in Javanese society are expansive. alone had an effect on the religious system. Scholars who understood Sanskrit were finally able to process Hindu-Buddhist letters to write Javanese.